Economic growth and integration in Central America - Desruelle, Dominique (IMF WashingtonUS, 2007)
Covers a number of policy priorities, including measures to increase the region's growth potential to narrow the income gap with more developed countries, ensure the sustainability of public pension systems, improve the structure and functioning of public debt markets and increase the effectiveness of monetary policy.